2003
DOI: 10.1161/01.cir.0000097111.00170.7b
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Contractile Reserve by Dobutamine Stress Echocardiography Predicts Improvement in Ejection Fraction With β-Blockade in Patients With Heart Failure

Abstract: MS; for the BEST InvestigatorsBackground-␤-Blockers improve survival and reduce hospitalization in chronic heart failure (CHF) by biologically improving left ventricular ejection fraction (LVEF). However, a good predictor of improvement with this therapy has not been identified. This substudy of BEST examined whether myocardial contractile reserve, as determined by dobutamine stress echocardiography, predicts improvement in LVEF. Methods and Results-Seventy-nine patients with class III/IV CHF underwent dobutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…The present study could not confirm previous results (6,7) showing that cardiac contractile reserve during dobu- tamine stress is useful for predicting the efficacy of b-blockers in patients with IDC and heart failure. There are several explanations for this discrepancy.…”
Section: Contractile Reserve and Dlvef-carvedilolcontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study could not confirm previous results (6,7) showing that cardiac contractile reserve during dobu- tamine stress is useful for predicting the efficacy of b-blockers in patients with IDC and heart failure. There are several explanations for this discrepancy.…”
Section: Contractile Reserve and Dlvef-carvedilolcontrasting
confidence: 99%
“…These factors might explain the failure of DLVEF-dobutamine to demonstrate a relationship to DLVEF-carvedilol. However, a low-dosage infusion protocol (10-20 mg of dobutamine per kilogram per minute) has been established to evaluate contractile reserve in previous studies (6,7).…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inotropic stimulation with dobutamine is an accepted alternative to exercise stress in the evaluation of left ventricular contractile reserve across a range of underlying pathologies including ischaemic heart disease, idiopathic dilated cardiomyopathy and valvular heart disease [8][9][10]. In contrast, only limited studies have addressed RV contractile reserve and these have predominantly been in the setting of biventricular failure [7,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Dobutamine detects myocardial contractile reserve 21,22 ; on the other hand, exercise predicts global cardiac capacity with increased LV preload and afterload. 13 It has been shown that exercise stress increases FMR 7,12,13 because it (1) increases the LV preload due to increased venous return, (2) increases systemic vascular resistance in conjunction with the autonomic nervous system, (3) causes an increase in LV sphericity, 12 and (4) dilates the MA.…”
Section: Comparing Exercise and Dobutamine Stress Echocardiography Inmentioning
confidence: 99%